ANALYSIS OF PUBLIC SERVICE QUALITY FOR VULNERABLE GROUPS AT THE INVESTMENT AND ONE-STOP INTEGRATED SERVICES OFFICE OF BALIKPAPAN CITY, EAST KALIMANTAN - Revi Citrawaty Hs.; Milwan; Roni Ekha Putera (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to analyze the implementation of public services for vulnerable groups at the Balikpapan City Investment and One-Stop Integrated Services Agency (DPMPTSP). Vulnerable groups include people with disabilities, the elderly, pregnant women, and low-income communities, who often face various obstacles in accessing public services. This study used a qualitative approach with descriptive-analytical methods. Data collection was conducted through in-depth interviews with DPMPTSP officers, vulnerable groups, and relevant stakeholders, direct observation of the service process, and analysis of documents related to public service policies. The results indicate that the Balikpapan City DPMPTSP has implemented several service innovations, such as priority counters and online services, to facilitate vulnerable groups. However, several obstacles remain, such as limited human resources who understand the special needs of vulnerable groups, infrastructure that is not yet fully disability-friendly, and a digital divide that impacts access to online services. This study recommends increasing human resource capacity through sensitivity training for vulnerable groups, improvements to physical and digital infrastructure, and collaboration with community organizations to ensure inclusive and equitable public services. Implementing these recommendations is expected to improve the quality of public services and ensure that vulnerable groups' rights to access public services are fulfilled.